A Cross-sectional study on the association between proximity to tobacco industrial area in La Union and the prevalence of resoiratory symptoms among adults - Estolero, Diana F. (2017.)
This study investigated the association between proximity to the tobacco industrial area and the prevalence of respiratory symptoms among adults in La Union. The study focused on the respiratory health symptoms as a potential health effects of living close to tobacco processing plants. Random samples of adults aged 18 years and above were drawn from the spot maps of the 10 communities bordering on the tobacco processing plants. Proximity to industry was used as a surrogate for exposure to air emissions from the tobacco industrial area. The study population area was grouped by the distance from the industry. The finding of the study suggested that those living within 1000 meters away from the tobacco industrial area had an elevated risk of having at least one respiratory symptom than those living farther. The risk of having cough was found higher among males living within 1000 meters away from the tobacco industrial area than those males living farther, however, the result is not statistically significant. There is a 28% and 33% increase risk of having sinusitis and sore throat respectively among those living within 1000 meters away from the tobacco industrial area than those living farther. However, the results are not statistically significant. The result of the study is suggestive but not sufficient to infer a causal relationship between living in proximity of tobacco industrial area and the respiratory health symptoms of the residents.
Available in CD, pdf copy.
Thesis (Master of Science in Public Health, Environmental Health)--University of the Philippines Manila.
Keywords: Tobacco smoke pollution; Respiratory organs -- Diseases